Skrining Anemia Remaja Putri SMKN 1 Negara Kabupaten Jembrana - Dewi, Asri; Daryaswanti, Daryaswanti; Febianingsih, Febianingsih; Nopiyanti, Nopiyanti; Astutik, Astutik; Sulistyadewi, Sulistyadewi (Jurnal SOLMA, 2024)
Background: The upstream problem of stunting is targeting the female adolescent age group. Health status, especially iron intake, is an important factor in efforts to prevent the risk of stunting. This activity aims to determine the incidence of anemia in adolescent girls as an initial step in checking the health of adolescent girls to prevent the risk of stunting, through a Hemoglobin check at SMKN 1 Negara Jembrana, Bali. Method: Anemia screening activities are carried out through health education using interview methods, questions and answers and the practice of checking hemoglobin levels, as well as recording the results of the examination. Counseling activities, while Hemoglobin and anthropometry examinations were carried out by the PkM Stikes KESDAM IX/Udayana team and assisted by community health centers and youth posyandu cadres. Result: There was an increase in the knowledge of young women before and after being given health education, from 58% to 905. Anemia screening activities obtained data. Most of the 79% of young women did not experience anemia, while 21% had anemia. Of the number of young women who experience anemia, 51% have mild anemia and 49% have moderate anemia. Conclusion: Counseling activities can increase knowledge, while anemia screening activities in adolescent girls show the real condition of hemoglobin levels in adolescent girls, so that they can become data for follow-up efforts.